EARLY ASSESMENT ON COMMON MENTAL DISORDERS OF PREGNANT WOMEN USING SELF-REPORTING QUESTIONNAIRE (SRQ-20) - Qomari, Selvia Nurul; Setiawati, Iin; Antina, Rila Rindi; Nikmah, Nurun (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
During pregnancy, women may experience physical and psychological changes that can make them vulnerable to mental health disorders, also known as CMD. This can have a significant impact on both the mother and the child's health, making it a public health concern. To address this issue, a study was conducted on pregnant women attending classes at the Arosbaya Community Health Center. The study used the Self-Reporting Questionnaire (SRQ-20) to collect data on CMD. The results showed that 40% of pregnant women suffer from CMD, with decreased energy and anxiety being the most common symptoms. It is crucial for healthcare professionals to prioritize the mental well-being of pregnant women and take steps to alleviate the symptoms of psychological disorders.